WHY DO PEOPLE DECIDE TO BUY FROM SHOPEE? AN EMPIRICAL STUDY ON THE INFLUENCE OF TRUST, SECURITY, E-SERVICE QUALITY AND RISK PERCEPTION IN PEKANBARU - ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 5 No 1 (2025): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to answer the question of why people in Pekanbaru choose to shop at Shoope? by using trust, security, electronic service quality and risk perception as causal factors. Based on 200 respondents who are Shopee users in Pekanbaru and using multiple linear regression analyses, the results showed that trust and service quality have a significant influence on the purchase decision, while security and risk do not have a significant influence on the purchase decision. Of the four factors tested, trust has the greatest influence on consumers' purchasing decisions at Shopee in Pekanbaru.